2020
DOI: 10.1038/s41594-020-00522-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of auto-inhibition and activation of Mec1ATR checkpoint kinase

Abstract: In response to DNA damage or replication fork stalling, the basal activity of Saccharomyces cerevisiae Mec1 ATR is stimulated in a cell cycle dependent manner, leading to cell cycle arrest and promoting DNA repair. Mec1 ATR dysfunction leads to cell death in yeast and causes chromosome instability and embryonic lethality in mammals. Thus, ATR is a major target for cancer therapies in homologous recombination-deficient cancers. Here we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 78 publications
3
39
0
Order By: Relevance
“…This effect induces an enclosed nucleotide-binding pocket that enhances ATP binding and hydrolysis (Fig. 3) (Tannous et al, 2021). This activation model is similar to another previous model, in which the potential charge-charge interaction between the AAD of Dpb11 and PRD is capable of destabilizing the interaction between PRD-I and the activation loop to eliminate the PRD-I block (Wang et al, 2017).…”
Section: Atrsupporting
confidence: 83%
See 3 more Smart Citations
“…This effect induces an enclosed nucleotide-binding pocket that enhances ATP binding and hydrolysis (Fig. 3) (Tannous et al, 2021). This activation model is similar to another previous model, in which the potential charge-charge interaction between the AAD of Dpb11 and PRD is capable of destabilizing the interaction between PRD-I and the activation loop to eliminate the PRD-I block (Wang et al, 2017).…”
Section: Atrsupporting
confidence: 83%
“…The Mec1-Ddc2 structure forms a similar butterfly shape as seen in ATM/Tel1, forming a dimer of a heterodimer with two-fold rotational symmetry in a head-to-head manner (Fig. 1F) (Tannous et al, 2021;Wang et al, 2017). The cryo-EM reconstructions of Mec1-Ddc2 have revealed that the activation loop attaches to the PRD insert (PRD-I), which seems to be key to inhibiting substrate access (Tannous et al, 2021;Wang et al, 2017).…”
Section: Atrmentioning
confidence: 82%
See 2 more Smart Citations
“…Human and yeast ATR-ATRIP complexes form a dimeric butterfly-like structure similar to ataxia telangiectasia mutated (ATM) with two ATR molecules and two ATRIP molecules in a single complex ( 19 , 20 , 21 , 22 , 23 ), and dimerization of the complex is required for function ( 24 ). ATM is activated by the MRE11-RAD50-NBS1 (MRN) complex ( 25 , 26 ), and like ATM, MRN is a dimer with two MRE11, RAD50, and NBS1 molecules in a single complex ( 27 ).…”
mentioning
confidence: 99%